Das NetzDG in der praktischen Anwendung Eine Teilevaluation des Netzwerkdurchsetzungsgesetzes - Liesching, Marc (Schriftenreihe Medienrecht & Medientheorie, 2021)
What are the practical effects of the Network Enforcement Act, which came into force in 2017 and was controversial from the start? Which compliance structures have the big three social networks Facebook, YouTube and Twitter implemented with regard to the removal of illegal user content? In addition to a presentation and evaluation of previous studies, monitoring reports and NetzDG reports from the social networks, possible criteria for "over-blocking" are identified and subsumed in this third volume of the series. On the occasion of the NetzDG evaluation commissioned by the federal government, the study was carried out additionally and independently of this. It is not based on any commissioning by public or private bodies.